FRESH perspectives: A practical session on integrating lived experiences into food environments research - Salm, Leah (Institute of Development Studies, 2024)
As part of the FRESH project researchers at the Institute of Development Studies and Colombo Urban Lab have developed an integrated approach of assessing food environments to understand community and vendor lived experiences, as well as the needs and priorities of different stakeholders. These data have been layered in an engaging way to draw viewers in, and showcase the various stories of individuals and localities, with the aim to stimulate policy action.